The Relationship Between Teacher Accountability Measures and Self-Efficacy - (:unkn) unknown (My University, 2017)
This study was designed to critically analyze teacher accountability and evaluation systems that are being utilized nation-wide, to discover how the systems impact teacher self-efficacy. One hundred thirty-two teachers from a large, diverse Wisconsin school district participated in a longitudinal study. The participants completed surveys at two time points (fall and spring) including collective efficacy, teacher self-efficacy, and sources of efficacy measures. A 2 x 2 mixed ANOVA showed no significant interaction between summary year status and changes in teacher self-efficacy. A multiple regression analysis revealed that sources of teacher self-efficacy included in the evaluation system positively predicted teacher self-efficacy when all of the sources were working together, and when student demographic factors were held constant. An independent samples t-test compared experiences of the sources of self-efficacy of teachers who were on-summary year to teachers who were off-summary year according to the evaluation system. Contrary to predications, the results indicated that teachers who were off-summary year reported more frequent and valuable experiences of the sources of self-efficacy, particularly in social persuasion, than teachers who were on-summary year. Also, this study analyzed the relationship between school context (collective efficacy and student demographics) and the relationship to teacher self-efficacy. The results from this study support the need for meaningful evaluation and accountability systems that provide opportunities for experiences and reflection on the four sources of self-efficacy. The results also indicate that there is a need to ensure proper implementation of such systems, as teachers on-summary year should have frequent experiences of social persuasion that they find value in. Themes in participant responses are used to provide recommendations for administrative implementation of the evaluation systems. The results additionally confirm a possible reciprocal relationship between collective efficacy and teacher self-efficacy. This suggests that providing a focus on supporting teacher self-efficacy can positively impact the school culture, which can also lead to more positive implementation of evaluation systems. Finally, the results suggest that student ethnic diversity and economic disadvantage positively impacts teacher self-efficacy, whereas teachers exposed to a more diverse student populations and more students with economic disadvantage reported higher teacher self-efficacy. English language learners and students with disabilities populations negatively predicted teacher self-efficacy. Future research is needed to investigate reasons for differences in reports of social persuasion between on-summary year and off-summary year teachers.
Keywords: Accountability; Evaluation; Self-Efficacy; Teacher